Physiological characteristics of elite professional soccer teams of different ranking - Kalapotharakos, V. I.; Strimpakos, N.; Vithoulka, I.; Karvounidis, C.; Diamantopoulos, K.; Kapreli, E. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: Few studies have examined the role of physiological characteristics of soccer teams in the finishing position in the league. The purpose of the present study was to investigate whether there are differences in anthropometric characteristics, endurance, isokinetic peak torque, vertical jump height among professional soccer teams with different rank in the Greek championship. Methods: Three soccer teams that participated in the Greek Championship participated voluntarily in the present study. The B (n=19; 26±4 years; 180±5 cm; 78±4.5 kg) team was among the best three teams of the National Greek league, whereas M (n=15; 24±4 years; 178±4 cm; 74.8±4.2 kg) and L (n=20; 23±3 years; 179±7 cm; 75.3±6.4 kg) teams were in the middle and last of the rank, respectively. All teams were evaluated in body fat (%), peak torque of knee extensors at 1.05 rad/s, running velocity at the lactate threshold (LT) and countermovement jump height. Results: The B team, which was deemed among the best three team of the league, presented significantly (P<0.05) lower body fat (%) values, and higher peak torque of knee extensors, running velocity at the LT, and vertical jump height values in comparison to the middle and last team of the league. Conclusion: The findings of the present study suggest that the physiological characteristics may play an important role for high soccer performance, as it is reflected from the rank order placed in the Greek championship. Especially, body fat (%), running velocity at the LT, peak torque of knee extensors and vertical jump ability could be differentiating factors for a soccer performance.